Economic Crisis in Portugal - Who Is to Blame? A Comparative Analysis between Political Responsibility and Public Perceptions (2008-2019) - Cunha, C.; Lobo (ECPR General Conference, 2021)
The global economic and financial crisis that originated in 2008 in the United States, triggered by the bankruptcy of the Lehman Brothers Bank, had negative effects on several financial institutions worldwide, a process that became known as the subprime loan crisis and had a powerful negative impact on the Portuguese economy. The calamity broadly affected Europe and became a debt crisis as of 2009 that precipitated bailouts from Greece and Ireland in May and November 2010 to April 2011 in Portugal. Thus, began the so-called Eurozone crisis in Europe. The main credit agencies downgraded Portugal’s sovereign rating, and yields on government debt rose sharply. The authorities requested financial assistance from the troika, which ultimately led to the program that began in May 2011. Politicians took a stand concerning the crisis and presented alternatives. Citizens also voiced their concerns regarding who was responsible for the predicament. This analysis examines on whom lay the responsibility for the economic crisis in Portugal beginning in 2008 and ending in 2016 by focusing on the voters and politicians’ perspectives (electoral candidates and elected MPs). The methodology is based on data from our participation in Freire, A.; Lisi, M.; Tsatsanis, E.; Viegas, J.M.L; and Correia, A. (2018), “Merged Data: Portuguese Citizens, MPs and Candidate Surveys 2008-2018,” research project at CIES-IUL and IPRI-NOVA, “Crisis, Political Representation and Democratic Renewal: The Portuguese case in the Southern European context,” FCT: PTDC/IVC-CPO/3098/2014 to demonstrate how candidates and members of parliament’s views of the economic crisis compare to the general public´s.